The HIPC initiative and poverty reduction in Ghana: An assessment - Robert Osei; Peter Quartey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper presents a review of the current debt problem in Ghana and assesses whether debt relief under the HIPC initiative can be effectively translated into poverty reduction. The extent of the debt burden is jeopardizing Ghana's effort at poverty reduction. The evidence suggests that debt relief could have a positive effect on poverty reduction in Ghana, although the effect will be small relative to say, export growth. Ghana cannot achieve significant improvements in its human development indicators if all the savings from debt relief are redirected to only primary health and education, as these sub-sectors already absorb a significant proportion of their sectoral budgets. Rather, the resources saved must be directed towards an integrated programme for the education and health sectors as a whole. The effectiveness of debt relief for poverty reduction will be greatly enhanced if it is duly complemented with proper fiscal management. – debt ; poverty reduction ; government expenditure
Keywords: F34; O11; O55; 330; Auslandsverschuldung; Schuldenerlass; Armutspolitik; Ghana